2018
DOI: 10.1130/g40153.1
|View full text |Cite
|
Sign up to set email alerts
|

Metallic iron formed by melting: A new mechanism for magnetic highs in pseudotachylyte

Abstract: Previous studies of rock magnetism in fault rocks imply frictional heating temperatures from ~300 °C to ~700 °C, which are far below the temperatures needed to form pseudotachylyte. Here, heating experiments were performed at elevated temperatures (as high as 1750 °C) on cataclasites from the Wenchuan Earthquake Fault Scientific Drilling borehole 2 (WFSD-2) cores, Longmen Shan thrust belt, China. Based on microstructural, geochemical, and rock magnetic analyses, the main conclusions are as follows. The melting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…It is supported by simulated experiments of quenched synthetic glasses (Schlinger & Smith, 1986). Recently, Zhang et al (2018) reported that metallic iron spherulites in a broad grain-size distribution could be formed in pseudotachylyte by cooling the melted cataclasite from high temperatures (>1300°C), also supporting the above model. Thus, similar precipitates can be produced by all kinds of volcanic eruptions; they persist because being included in glass or silicate crystals harnesses them from further pedogenic and other alteration processes.…”
Section: Magnetic Domain-size Behaviorsupporting
confidence: 68%
“…It is supported by simulated experiments of quenched synthetic glasses (Schlinger & Smith, 1986). Recently, Zhang et al (2018) reported that metallic iron spherulites in a broad grain-size distribution could be formed in pseudotachylyte by cooling the melted cataclasite from high temperatures (>1300°C), also supporting the above model. Thus, similar precipitates can be produced by all kinds of volcanic eruptions; they persist because being included in glass or silicate crystals harnesses them from further pedogenic and other alteration processes.…”
Section: Magnetic Domain-size Behaviorsupporting
confidence: 68%
“…Liu et al, 2014D. Liu et al, , 2016Mishima et al, 2006Mishima et al, , 2009Nakamura et al, 2002;Pei, Li, et al, 2014;Tanikawa et al, 2007Tanikawa et al, , 2008Yang et al, 2012aYang et al, , 2012bYang et al, , 2018Yang et al, , 2019Yang, Chen, et al, 2013;Yang, Mishima, et al, 2013;Yang, Dekkers, & Zhang, 2016;Zhang et al, 2017Zhang et al, , 2018. By providing a trove of information on physical and chemical processes associated with faulting in seismically active zones, these pioneer works have laid the foundation of "fault magnetism", an emerging subdiscipline in the geosciences.…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%
“…The oxygen fugacity in the highly localized melt pockets is generally 2-4 log units above the fayalite-magnetite-quartz buffer (~−11 log units at ~1000°C and 110-160 MPa, e.g., O'Hara & Huggins, 2005). Pseudotachylytes are often more magnetic than their parent rocks, due to the presence of fine-grained PSD/SD ferrimagnetic minerals, predominantly magnetite, that form due to oxidation of mafic silicates during the melting and subsequent quenching (Ferré et al, 2005(Ferré et al, , 2012(Ferré et al, , 2017Ferré, Geissman, et al, 2014;Nakamura et al, 2002;O'Hara, 2001;Pittarello et al, 2012;Zhang et al, 2018). This enables a potentially excellent recording of the NRM in the pseudotachylytes during cooling through the blocking temperature, that is, the NRM is a TRM and should be considered a primary remanence, representing the time of pseudotachylytes cooling, that is, shortly after the rupture itself.…”
Section: Coseismic Frictional Melting With Pseudotachylyte Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative explanation for the high susceptibility in the altered pseudotachylytes is the formation of metallic iron during faulting. Zhang et al (2018) have noted formation of micron-sized iron spherules in pseudotachylytes that were heated within a range of 1300-1500 • C, leading to increased magnetic susceptibility. However, no such spherules are directly observed with scanning electron microscopy ( Fig.…”
Section: Source Of Magnetic Susceptibility and Its Anisotropymentioning
confidence: 99%